2018
DOI: 10.1159/000495101
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of mRNAs and lncRNAs of Intramuscular Fat Related to Lipid Metabolism in Two Pig Breeds

Abstract: Background/Aims: Long non-coding RNAs (lncRNAs) can regulate adipogenesis and lipid accumulation. Intramuscular fat deposition appears to vary in different pig breeds, and the regulation mechanism has not yet been fully elucidated at molecular level. Moreover, little is known about the function and profile of lncRNAs in intramuscular fat deposition and metabolism in pig. The aim of this study was thus to explore the regulatory functions of lncRNAs in intramuscular fat deposition. Methods: In this study, Laiwu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 63 publications
5
41
0
Order By: Relevance
“…In terms of conservation between species, lncRNAs were also far less conserved than mRNAs. The lncRNAs obtained through RNA-seq were roughly the same in terms of length, number of exons, and conservation, as those found in previous studies on porcine adipose tissues [19] and intramuscular fat [20]. KEGG analysis showed that the target genes of these lncRNAs were enriched in some classical signaling pathways related to fat formation, in ammation, and growth.…”
Section: Lnc_000368 Promotes Intramuscular Adipocyte Differentiationsupporting
confidence: 73%
“…In terms of conservation between species, lncRNAs were also far less conserved than mRNAs. The lncRNAs obtained through RNA-seq were roughly the same in terms of length, number of exons, and conservation, as those found in previous studies on porcine adipose tissues [19] and intramuscular fat [20]. KEGG analysis showed that the target genes of these lncRNAs were enriched in some classical signaling pathways related to fat formation, in ammation, and growth.…”
Section: Lnc_000368 Promotes Intramuscular Adipocyte Differentiationsupporting
confidence: 73%
“…Excessive SC fat deposition greatly decreases the growth performance and meat production efficiency, which results in profit reduction [7,8]. However, Chinese indigenous pig breeds often exhibit better fertility, disease resistance and IM fat content than foreign pig breeds [9][10][11]. Understanding the porcine adipocyte regulation network to decrease SC fat deposition is a key issue in genetic improvement of Chinese indigenous pig breeds.…”
mentioning
confidence: 99%
“…However, the redundant SC fat deposition decreases the growth efficiency and results in profit reduction. By contrast, Large White pig is the most widely distributed lean-type pig breed with relatively low SC fat deposition [11]. In this study, highthroughput RNA-seq was conducted to compare the gene expression profiles of differentiated SC adipocytes from the two pig breeds.…”
mentioning
confidence: 99%
“…Sallam et al found that MeXis can enhance the expression of ABCA1 by regulating the chromatin structure of ABCA1, while suppression of MeXis can accelerate the formation of foam cells and promote AS formation in Apoe −/− mice (Sallam et al, 2018). Using pigs as a model to study fat formation and lipid metabolism, Huang's team found that 55 lncRNAs were differentially expressed between Laiwu and Large White (Large Yorkshire) pigs (Huang et al, 2018). XLOC_046142, XLOC_004398, and XLOC_015408 were hypothesized to play a key role in the regulation of fat formation and lipid accumulation in pig muscle tissues, while LOC_064871 and XLOC_011001 may play a role in diseases related to lipid metabolism.…”
Section: Lncrnas In Lipid Metabolismmentioning
confidence: 99%